Initial presentation for acute low back pain: is early physical therapy associated with healthcare utilization and spending? A retrospective review of a National Database - Majd Marrache; Niyathi Prasad; Adam Margalit; Suresh K. Nayar; Matthew J. Best; Julie M. Fritz; Richard L. Skolasky (BMC, 2022)
Abstract Background Early initiation of physical therapy (PT) has been associated with lower healthcare costs and utilization; however, these studies have been limited to single institutions or healthcare systems. Our goal was to assess healthcare utilization and spending among patients who present for the first time with low back pain (LBP), according to whether they received early physical therapy (PT), using a large, nationwide sample; and geographic variation in rates of early PT and 30-day LBP-related spending. Methods Using the Truven MarketScan database, we identified nearly 980,000 US adults ages 18-64 years who initially presented with acute LBP from 2010 through 2014 and did not have nonmusculoskeletal causes of LBP. Approximately 110,000 patients (11%) received early PT (≤2 weeks after presentation). We compared healthcare utilization and spending at 30 days and 1 year after presentation between patients who received early PT and those who did not. Alpha = 0.05. Results At 30 days, early PT was associated with lower odds of chiropractor visits (odds ratio [OR] = 0.41, 95% confidence interval [CI] = 0.40-0.42), pain specialist visits (OR = 0.49, 95% CI = 0.47-0.51), emergency department visits (OR = 0.51, 95% CI = 0.49-0.54), advanced imaging (OR = 0.57, 95% CI = 0.56-0.58), orthopaedist visits (OR = 0.67, 95% CI = 0.66-0.69), and epidural steroid injections (OR = 0.68, 95% CI = 0.65-0.70). At 1 year, early PT was associated with less healthcare utilization. At 30 days, patients with early PT had lower mean LBP-related spending ($1180 ± $1500) compared with those without early PT ($1250 ± $2560) (P < 0.001). At 1 year, LBP-related spending was significantly less among patients who did not receive early PT ($2510 ± $3826) versus those who did ($2588 ± $3704). Early PT rates (range, 4-25%; P < 0.001) and 30-day LBP-related spending differed by state (range, $421 to −$410; P < 0.001). Conclusion Early PT for acute LBP was associated with less 30-day and 1-year healthcare utilization and less 30-day LBP-related spending. Early PT rates and 30-day spending differed by US state. Level of evidence IV